Capturing the Asymmetrical Effect of Macroeconomic Factors on Public-Sector Innovation in Chinese Local Government: A Dynamic Technology Forecasting Approach - You, Chengde; Khattak, Shoukat Iqbal; Ahmad, Manzoor (SAGE open, 2024)
Despite the considerable investments in Chinese public sector innovation in China and its social impact, there is insufficient information on how asymmetries in macroeconomic factors and business cycles affect public sector innovation. Based on provincial data from thirty regions (2000–2016), the study proposes a dynamic model to capture the asymmetrical impact of macroeconomic factors on local government innovation. The innovation-based predictive model indicated that a positive shock to macro-economic factors (i.e., gross domestic product, government administration expenditures, provincial degree of openness in economies, provincial degree of openness in society, higher education research and development expenditures, local revenue, and local expenditure) upsurge government innovation. In contrast, a negative shock to these factors disrupts local government innovation. Third, the model indicated a pro-cyclical relationship between positive and negative shocks to government administration expenditures and provincial government innovation during the boom and recession periods. The study offers an essential policy tool and some important implications for local government officials, future researchers, and policymakers to understand how cyclic and asymmetric behavior in local government innovation shapes the innovation efficiency of the public sector in China. Subject Classification Codes: O30, O31, O32, 01, O38, O36, O35, O38, P25, Q01, H72. Plain language summary The study proposes a dynamic framework to capture the asymmetrical impact of macroeconomic factors on local government innovation. Provincial data (2000–2016) from thirty regions of China were analyzed using a non-linear Auto Regressive Distributed Lag panel-based model. The results indicated that a positive shock to macro-economic factors (i.e., gross domestic product, government administration expenditures, provincial degree of openness in economies, provincial degree of openness in society, higher education research and development expenditures, local revenue, and local expenditure) had upsurged government innovation, even though a negative shock had disrupted local government innovation. A pro-cyclical relationship was observed between positive and negative shocks to government administration expenditures and provincial government innovation during the boom and recession periods respectively. The study offers an essential policy tool and some important implications for local government officials, future researchers, and policymakers to understand how cyclic and asymmetric behavior in local government innovation shapes the innovation efficiency of the public sector in China. Of some limitations that offer future research avenues, this study only explored the connection between selected macroeconomic factors for China. Comparative or single-country studies may be conducted for local governments in other emerging economies, including African nations, Asian countries, European states, OECD nations, G7 countries, and BRICS states.